Direct Support to Private Firms : Evidence on Effectiveness - Batra, Geeta; Mahmood, Syed (World Bank, Washington, DC, 2014)
Governments use a variety of instruments to provide direct support to private enterprises. These include the provision of finance (subsidized and/or directed credit) and business development services (management and marketing advice to small businesses, agricultural extension services, support for enterprise level training and support to technology development). These interventions are distinct from those that support enterprises indirectly by establishing a policy and legal environment conducive to enterprise development. How effective have these direct support schemes been? This paper attempts to provide some answers to this question by surveying the available literature on the effectiveness of direct support interventions. Where available, impact evaluations suggest that the performance has been mixed at best. The evidence indicates that active intervention does not work unless the basic environment for private sector development is sound. Public policy thus needs to focus on creating an enabling environment, key elements of which include a sound legal and judicial system which supports low-cost contract enforcement, good infrastructure, a policy playing field which is level in terms of ease of registration, taxes and investment incentives for all enterprises-large and small, domestic and foreign.